Changing Profile of Herpes Zoster in Nepal: A Hospital-Based Study - Kayastha, BMM; Shrestha, Pallem; Shrestha, R; Lama, L (Nepal Journal of Dermatology, Venereology & Leprology, 2012)
Keywords: Herpes zoster; Clinico-epidemiological profile; dermatomes DOI: http://dx.doi.org/10.3126/njdvl.v8i1.5710 Nepal Journal of Dermatology, Venereology & Leprology 8(1) 2009 1-4